The Childfree Phenomenon: Perspectives from Hadith and Sociology - Prasetiyo, Joko Roby; Laksono, Krisbowo (Pascasarjana UIN Raden Mas Said Surakarta, 2023)
This research aims to explore the perspectives of religion and sociology on the Childfree phenomenon. The study adopts a qualitative approach using the methodology of Conceptual Thematic Hadith Studies and Sociology. The research findings and discussions reveal both theological and social understandings. Based on the exploration of hadiths concerning marriage and procreation, the decision not to have children (Childfree) within marital relationships can undermine one of the primary purposes of marriage, which is reproduction. Having children in Islamic doctrine carries implications for both worldly life and the hereafter. The directives in the hadiths regarding marriage and procreation are recommendations and forms of preference rather than obligatory commands. From a sociological perspective, the choice of spouses to be Childfree represents a social reality that is currently occurring. The decision to be Childfree, for any reason, contradicts the values believed and understood by the majority of Indonesian society, which consider reproduction as a significant purpose of marriage.